FORMATION OF DIALOGUE SKILLS OF STUDENTS FROM INVOLVING THEM IN ACTIVE EDUCATIONAL DIALOGUE - L.V. Burman (Academy of Cognitive and Natural Sciences, 2002)
The verified method of the students' inclusion into active dialogue providing the efficiency of dialogue skills development is suggested.